2018
DOI: 10.1007/s10456-018-9596-7
|View full text |Cite|
|
Sign up to set email alerts
|

Soluble delta-like 1 homolog (DLK1) stimulates angiogenesis through Notch1/Akt/eNOS signaling in endothelial cells

Abstract: The present study unveils the pro-angiogenic function and mechanism of soluble DLK1 through activation of Notch1 signaling in endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 43 publications
0
34
1
1
Order By: Relevance
“…Whether the VEGFR2 signal is activated, we detected the phosphorylation level of VEGFR2 after activating CD137 signaling for a time point, 0, 2, 5, 10, 15, and 30 minutes and found that phosphorylated VEGFR2 (Tyr1173) was increased, achieving the maximum level at 10 minutes, which indicated that CD137 rapidly promoted VEGFR2 phosphorylation at Tyr1173 (Figures 2(d) and 2(e) ). Besides, activating the CD137 signal for 10 minutes promoted Akt and eNOS phosphorylation (Figures 2(f) and 2(g) ) both the downstream molecules of phosphorylated VEGFR2 [ 39 ]. And blocking CD137 signaling with inhibitory anti-CD137 antibody weakened the effects of CD137 signaling on VEGFR2 and Phospho-Akt (p-Akt, Ser473) and phospho-eNOS (p-eNOS, Ser1177) (Figures 2(f) and 2(g) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the VEGFR2 signal is activated, we detected the phosphorylation level of VEGFR2 after activating CD137 signaling for a time point, 0, 2, 5, 10, 15, and 30 minutes and found that phosphorylated VEGFR2 (Tyr1173) was increased, achieving the maximum level at 10 minutes, which indicated that CD137 rapidly promoted VEGFR2 phosphorylation at Tyr1173 (Figures 2(d) and 2(e) ). Besides, activating the CD137 signal for 10 minutes promoted Akt and eNOS phosphorylation (Figures 2(f) and 2(g) ) both the downstream molecules of phosphorylated VEGFR2 [ 39 ]. And blocking CD137 signaling with inhibitory anti-CD137 antibody weakened the effects of CD137 signaling on VEGFR2 and Phospho-Akt (p-Akt, Ser473) and phospho-eNOS (p-eNOS, Ser1177) (Figures 2(f) and 2(g) ).…”
Section: Resultsmentioning
confidence: 99%
“…The deficiency in eNOS markedly decreased retinal neovascularization in a mouse model [ 55 ]. Additionally, Huang et al reported that soluble delta-like 1 homolog (DLK1) stimulated angiogenesis through Notch1/Akt/eNOS signaling in ECs [ 39 ]. CD137 signaling activating eNOS conforms to the studies on CD137 proangiogenesis effects [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous literature has stated that activation of the PI3K/AKT pathway can modulate migration and angiogenesis in endothelial cells . AKT activation gives rise to microvascular tube formation in endothelial cells, due to the response of VEGF stimulation . Another study has documented that activation of VEGFR2, which can be activated by VEGF, can induce activation of ERK .…”
Section: Discussionmentioning
confidence: 99%
“…There were no obvious changes among the control, CP and Meg3 groups. Under the acute cerebral infarction, the angiogenesis and the endothelial cells migration ability were reduced [28]. MPO brought stronger RBE4 migration ability comparing to the other groups.…”
Section: Mpo Target Rbe4 In Vitro and Down-regulated Meg3 Expressionmentioning
confidence: 82%